1st you must factor
x^2+3x-28
(x+7)(x-4)
you can check to see if you are right by using FOIL
First x*x Outer x*-4 Inner 7*x Last 7*-4
and you get x^2-4x+7x-28
combine like terms so you get x^2+3x-28
and you know you are right b/c you ended up wih what you started with
then you set each of the factored sets equal to 0 and solve
x+7=0 x-4=0
x=-7 x=4
2007-04-07 09:24:37
·
answer #1
·
answered by trn09 2
·
0⤊
0⤋
x^2 + 3x - 28 = 0
x^2 + 7x -4x - 28 =0
x ( x + 7 ) - 4 ( x + 7 ) = 0
x - 4 = 0 , x = 4
x + 7 = 0 , x = -7
2007-04-11 07:31:06
·
answer #2
·
answered by valivety v 3
·
0⤊
0⤋
This factors by inspection into (x+7)(x-4), so the roots are -7 and +4. Since the 28 is negative, you want two numbers whose difference is 3 and whose product is 28, and 4 and 7 work so all you need to do is to get the signs right. If this did not work, one can always use the quadratic formula.
2007-04-07 09:20:56
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
If these quadratics get too hard to solve by inspection I prefer to solve by completing the square as I can never remember the equation method.
x^2 + 3x - 28 = 0
x^2 + 3x = 28
add half the coeficient of x, squared, to both sides.
x^2 + 3x + (3/2)^2 = 28 + (3/2)^2
(x + 3/2)^2 = 30.25
x + (3/2) = +/- (sqrt 30.25)
x = sqrt 30.25 - (3/2) = 4
or x= -(sqrt 30.25) - (3/2) = -7
2007-04-07 09:38:48
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
(x+7)(x-4)
so x=-7 or 4
2007-04-07 09:23:07
·
answer #5
·
answered by FranklyTodd 2
·
0⤊
0⤋
x^2+3x-28=0
(x+7)(x-4)=0
x+7=0
x=-7
x-4=0
x=4
roots are -7, 4
2007-04-07 09:55:25
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
x² + 3x - 28
x² - 4x + 7x - 28
x(x - 4) + 7(x - 4)
(x + 7)(x - 4)
- - - - -
Roots
x + 7 = 0
x + 7 - 7 = 0 - 7
x = - 7
- - - - - -
Roots
x - 4 = 0
x - 4 + 4 + 0 + 4
x = 4
- - - - - - - - - -s-
2007-04-07 10:27:01
·
answer #7
·
answered by SAMUEL D 7
·
0⤊
0⤋
-7,4
2016-05-19 04:58:34
·
answer #8
·
answered by ? 3
·
0⤊
0⤋